Impact of space weather on the satellite industry. Issue 6 (26th June 2017) - Green, J. C.; Likar, J.; Shprits, Yuri
Abstract: This paper describes space weather impacts to the satellite infrastructure as perceived by satellite industry stakeholders. The information was gathered through in‐person and remote meetings with both satellite operators and manufacturers. The paper describes current impacts, industry processes for managing and mitigating impacts, costs, and industry needs and requirements. Lastly, we suggest potential improvements and solutions to problem areas based on our observation of the industry processes including (1) improved tools for quick anomaly attribution, (2) training, and (3) coordinated information sharing. Plain Language Summary: The highly variable space radiation environment around Earth can impact the global satellite infrastructure causing temporary malfunctions or permanent loss of satellite functions. International concern regarding this threat is growing as our technological society becomes ever more dependent on satellite capabilities. This paper describes space weather impacts as perceived by satellite industry stakeholders. The information was gathered through in‐person and remote meetings with both satellite operators and manufacturers. The paper describes current impacts, industry processes for managing and mitigating impacts, costs, and industry needs and requirements. Lastly, we suggest potential improvements and solutions to problem areas based on our observation of the industry processes including (1) improved tools for quick anomaly attribution, (2) training, and (3) coordinated information sharing. Key Points: Satellite industry stakeholders believe that most recent space weather impacts to satellites are not severe Some satellite anomalies may not be addressed because of the lack of tools for quick root cause attribution Satellite industry stakeholders requested guidance to set design specifications and tools to decide if an issue is space weather related